Participatory scenario development on the future of maize - mixed systems in East and Southern Africa - Nkanyani, S.; Mwamakamba, S.; Zimba, N. (International Water Management Institute (IWMI). CGIAR Initiative on Diversification in East and Southern Africa, 2024)
Recognizing the escalating pressures on the maize-mixed farming system in East and Southern Africa (ESA), the CGIAR Initiative on Diversification in East and Southern Africa convened a Regional Participatory Scenario Development Workshop through the collaborative efforts of the International Water Management Institute (IWMI) and its partners the Food, Agriculture and Natural Resources Policy Analysis Network (FANRPAN) and the International Food Policy Research Institute (IFPRI). This strategic initiative brought together key stakeholders to cocreate plausible future scenarios, exploring pathways towards a more diversified and resilient agricultural landscape.